HOW DOES STARBUCKS IMPLEMENT THE BLOCKCHAIN SYSTEM IN SUPPLY CHAIN MANAGEMENT TO MAINTAIN ITS PRODUCT QUALITY? - Valida Nur Shanti Ginting; Kees Tesselhof (Diponegoro Journal of Accounting, 2023)
In many different industries, including finance, healthcare, government, manufacturing, and distribution, the blockchain itself has taken on a life of its own and permeated a wide variety of applications. The optimal fusion of efficiency and transparency can be achieved by combining Supply Chain Management and Blockchain technology. In order to set itself apart from other coffee shops, Starbucks' quality control procedure is quite tight when choosing the raw materials used to produce its coffee products. Starbucks is able to uphold high product standards in any nation or city by using locally obtained ingredients and suppliers to preserve the quality of its products. This research also analyzed how blockchain positively impacts Starbuck's supply chain management to preserve product quality. This research uses the qualitative approach that collects primary data and secondary data. The coffee beans that Starbucks buys from its suppliers, however, must be roasted in the closest Starbucks roastery in the nation before being turned into beverages. Unfortunately, the majority of Starbucks locations in Asia are still lagging in the adoption of cutting-edge technologies like blockchain to support their supply chain management operations. One such location is Starbucks Indonesia. The conclusion is that incorporating a blockchain system into Starbucks's supply chain management could result in a multitude of positive outcomes for the company. The following recommendations for Starbucks Indonesia to consider when exploring the implementation of blockchain technology in its supply chain management Pilot Testing and Proof of Concept, Collaborate with suppliers and partners, Training and Education, and Continuous evaluation and improvement.